The Influence Of Religiosity And Optimism On The Resilience Of Msme Entrepreneurs: A Causal Experimental Study - Dian Fitri; Amin Akbar; Firunika Intan Cahyani (Universitas Muhammadiyah Gresik, 2025)
Background: The challenges after the Covid-19 pandemic for MSME entrepreneurs are like natural selection that tests patience and resilience in going through difficult times. Objective: This study aims to determine the level of religiosity and optimism towards the resilience of MSME actors forced by the Covid-19 pandemic. Method: This study is a causal experimental research where the research variables to be studied in this study consist of exogenous variables (religiosity and optimism), and also endogenous variables (resilience). The determination of the sample of this study is by using a non-probability sampling technique. This study uses the Resilience Scale of the Connor Davidson Resilience Scale (CD-RISC) which is adapted from the original scale in accordance with the aspects proposed by Connor and Davidson (2003). Result: (a) It can be seen that religiosity directly affects resilience significantly, namely p value (0.000 < 0.05) with an estimated value of 0.373. Judging from the positive value of the estimate, it can be concluded that the better the religiosity, the higher the resilience. (b) It can be seen that optimism directly affects resilience significantly, namely p value (0.000 < 0.05) with an estimated value of 1.256. Judging from the positive value of the estimate, it can be concluded that the better the optimism, the higher the resilience. Conclusion: Based on the results of the analysis carried out, it can be concluded that resilience in MSME actors can be influenced by religiosity and optimism.